Neospora caninum infection and reproductive disorders in Creole goats from southern Peru: a Bayesian mediation analysis across agroecological zones - Soca Jorge, Jhony (2026)
Background and Aim: Neosporosis, caused by Neospora caninum, is an important infectious cause of reproductive failure in ruminants, yet its epidemiological role in goats from hyper-arid coastal ecosystems remains poorly understood. In southern Peru, Creole goat production is predominantly extensive, with limited sanitary control and frequent dog–livestock interactions, which may facilitate parasite transmission. This study aimed to estimate the prevalence of N. caninum and evaluate its association with reproductive problems in Creole goats, considering age and agroecological zone within a Bayesian mediation framework. Materials and Methods: A cross-sectional analytical study was conducted between March and June 2025 in the Ica region of southern Peru. A total of 182 female goats from 28 herds with a history of reproductive disorders were included. Serum samples were analyzed using a competitive enzyme-linked immunosorbent assay to determine N. caninum serostatus. Reproductive problems, defined as abortion or the birth of weak offspring, were considered the outcome variable. Associations among age, geographic zone, infection status, and reproductive problems were assessed using a Bayesian mediation model to estimate direct, indirect, and total effects. Results: The prevalence of N. caninum was higher in Zone 1 (25.78%; 95% confidence interval [CI]: 18.57–33.58) than in Zone 2 (11.11%; 95% CI: 4.08–20.38). Seropositive goats exhibited a significantly higher likelihood of reproductive problems (odds ratio = 6.49; 95% highest posterior density: 1.76–16.11). Reproductive disorders were more frequent in Zone 2 despite its lower seroprevalence, indicating the influence of non-infectious factors. Age showed a significant positive association with reproductive problems, reflecting cumulative physiological and environmental stress. Mediation analysis revealed that N. caninum acted as a direct risk factor rather than a significant mediator of age- or zone-related effects. Conclusion: N. caninum infection is strongly associated with reproductive problems in Creole goats from southern Peru and primarily functions as an individual-level risk factor. Geographic and age-related effects appear to operate largely through direct pathways independent of infection status. These findings highlight the multifactorial nature of reproductive disorders and underscore the importance of integrating infection control with nutritional and management strategies in extensive goat production systems.